Indwelling tunneled pleural catheters in patients with hepatic hydrothorax: A single-center analysis for outcomes and complications. Issue 1 (2nd January 2023) - Alhabeeb, Fatmah F.; Carle-Talbot, Katia; Rakocevic, Natalie; Zhang, Tinghua; Mitchell, Michael; Amjadi, Kayvan; Kwok, Chanel
Abstract: Rationale: Patients with refractory hepatic hydrothorax (HH) are challenging to manage due to associated risks involved with repeated procedures required for drainage of the effusion. There is paucity of data describing the role of indwelling pleural catheters (IPC) in HH. We describe our experience with IPCs for management of refractory HH in collaboration with our homecare nursing services. Objective: We are describing our Canadian experience using IPCs for HH, focusing on outcomes, safety, and complications to improve the management of this condition. Methods: This is a retrospective study of a prospectively maintained database of all patients with HH who underwent IPC insertion between May 2006 and February 2019 at our tertiary center. Patients' characteristics, procedural variables, outcomes and estimated survival analysis post IPC insertion were analyzed. Measurements and main results: A total of 40 patients underwent 43 IPC insertions. Seven catheters (17.5%) resulted in pleural infection, without any associated deaths. Mean pleural fluid protein level was lower among patients who developed pleural infection compared to those who did not (11.5 g/L vs 16 g/L; p = 0.0015). Median survival was 12.7 months (95% CI, 6.4-43.4). Twenty-one catheters were removed within 149 days (+/- 50.2). Twelve patients died with the IPC in-situ within 69.5 days (+/- 48.7). Conclusion: In refractory HH, IPCs can be safely used. Associated complications can be mitigated with frequent clinical monitoring and intermittent drainage of the effusion by dedicated homecare nursing services. Further studies establishing the role for prophylactic antibiotics in high-risk population may be of value.